Photographic visualization of stories: documenting the experiences of people with intellectual disabilities with guided photovoice - Scheffers, Femke; Moonen, Xavier; van Vugt, Eveline (Journal of intellectual disabilities, 2025)
People with intellectual disabilities are often excluded from participation in research, whilst research has the potential to enhance positive change in their lives. In the current study, using a guided photovoice procedure, the experiences of people with intellectual disabilities regarding participation in research are evaluated. A total of 14 participants with intellectual disabilities were interviewed using guided photovoice. Through thematical analyses the experiences of people with intellectual disabilities regarding photovoice are discussed. Benefits were taking time, visual cues and the opportunity to speak out. Challenges were abstract concepts and aftercare. Guided photovoice helps to better understand the perspective of people with intellectual disabilities and thus can help to improve their quality of life. People with intellectual disabilities were interested in taking part in the current research project and experienced participating as a positive experience. However careful planning and expertise in communication with people with intellectual disabilities is necessary to include people with intellectual disabilities in research.